PENGGUNAAN MEDIA SOSIAL PADA REMAJA SOCIAL NETWORKING ADDICTION DI DESA LELEKA KECAMATAN WOLASI KABUPATEN KONAWE SELATAN - Adrian Tawai; Faturachman Alputra; La Ode Herman Halika; Fera Tri Susilawaty; Reski Reski; Marsela Marsela (Universitas Halu Oleo, 2022)
The purpose of this writing is to identify and provide an understanding of the Use of Social Media In Adolescent Social Networking Addiction In Leleka Village, Kec. Wolasi District, South Konawe. The method is through training, workshops, mentoring and evaluation as a concrete form of community service activities. The results of Community Service in Leleka Village, Wolasi District, South Konawe Regency are that adolescents can reduce the level of social networking addiction by removing social media installed on smartphones if using social media via a computer, turning off notifications while working, studying, or doing other important things, providing regular schedule for accessing social media, looking for fun or other activities outside of social media, leaving all gadgets in a separate room when hanging out with family, and visiting relatives and family in person to make relationships warm.